A kockázati- és magántőke-ágazat szerepe a gazdaságban - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
– Venture capital and private equity financing has become an important mechanism for the development and radical transformation of companies worldwide in recent decades. Nevertheless, the venture capital and private equity sector covers only a relatively small proportion of economic activity related to corporate financing. The two basic areas of venture capital and private equity industry are venture capital and buyouts. They play a key role in financing firms in radically different situations. The importance of venture capital and private equity as a financing intermediary channel can be measured in several ways. Its significance can be compared to the total amount of corporate financing or to the total value of publicly listed companies; however, it can also be characterized by its magnitude in relation to the generated volume of GDP generated in the given country. The importance of venture capital and private equity financing is reflected in the volume of capital raised by venture capital and private equity funds from institutional investors for investments, the amount of capital managed by the existing funds, the value of capital actually invested in each year and the number of companies financed by them in a year. Finally, the importance of venture capital and private equity investments can also be seen in the role the financed companies play in the economy, and also in the magnitude of changes they trigger in these companies. The study examines these relationships and effects in details.
Keywords: G24; G32; M13; O32; 330; venture capital; private equity; acquisition; entrepreneurship; innovation